Interacción Sino-Iberoamericana (Walter de Gruyter, 2021)
Sino-Iberoamerican Interaction provides a first-class academic platform for research on interactive relations between China and Spanish-Portuguese-speaking countries.
Keywords: China : Relations : Latin America : Periodicals; Latin America : Relations : China : Periodicals; China : Foreign economic relations : Latin America : Periodicals; Latin America : Foreign economic relations : China : Periodicals; China : Commerce : Latin America : Periodicals; Latin America : Commerce : China : Periodicals